Isolation of proteins on chromatin reveals signaling pathway-dependent alterations in the DNA-bound proteome - Wang, Huiyu; Syed, Azmal Ali; Krijgsveld, Jeroen; Sigismondo, Gianluca (Molecular & cellular proteomics, 2025)
Signaling pathways often convergence on transcription factors and other DNA-binding proteins that regulate chromatin structure and gene expression, thereby governing a broad range of essential cellular functions. However, the repertoire of DNA-binding proteins is incompletely understood even for the best-characterized pathways. Here, we optimized a strategy for the isolation of Proteins on Chromatin (iPOC) exploiting tagged nucleoside analogs to label the DNA and capture associated proteins, thus enabling the comprehensive, sensitive, and unbiased characterization of the DNA-bound proteome. We then applied iPOC to investigate chromatome changes upon perturbation of the cancer-relevant PI3K-AKT-mTOR pathway. Our results show distinct dynamics of the DNA-bound proteome upon selective inhibition of PI3K, AKT, or mTOR, and we provide evidence how this signaling cascade regulates the DNA-bound status of SUZ12, thereby modulating H3K27me3 levels. Collectively, iPOC is a powerful approach to study the composition of the DNA-bound proteome operating downstream of signaling cascades, thereby both expanding our knowledge of the mechanism of action of the pathway and unveiling novel chromatin modulators that can potentially be targeted pharmacologically.
Online verfügbar: 20. Januar 2025, Artikelversion: 19. Februar 2025
Gesehen am 30.09.2025